Association between Parenting Style and Language Development in Children: Parenting Style and Language Development - Sadiq, Sumaira; Farooq, Naima; Mansoor, Rabia; shoukat, Saadia; Saqulain, Ghulam (Pakistan Journal of Health Sciences, 2024)
Parenting style plays important role in the development of the children from birth to five years of age including language development as well. Hence, parents can play important role in the development of their children because their quality of time matters. Objective: To determine the association between parenting style and language development and to identify the type of parenting style mostly use by the parents. Methods: This cross-sectional study, with a sample of n=384 parents, was conducted at Riphah International University, Islamabad from 1st August, 2022 to 31st January, 2023. Parents of typical children of both genders, aged birth to 36 months were included. Basic demographical sheet, Parenting style questionnaire and Receptive Expressive Emergent Language (REEL)3rd edition were used for data collection. SPSS version 21.0 was used for data analysis. Point-Biserial Correlation was used to determine correlation between the parenting style and language development and p<0.05 was considered significant. Results: Results indicate significant (p<0.001) relationship between parenting style and language development of children. The correlation of parenting style was low with receptive language but high with expressive language. The results also indicate that parents used different parenting styles with majority 225(58.6%) using authoritative parenting style and least 12(3.1%) used permissive parenting style. Conclusions: Study concludes that parenting styles have great impact on language development of children. Different types of parenting style are being used among which authoritative parenting style is the most and permissive being the least common.